Chronic carbohydrate restriction improves endurance capacity and body composition in men and women - O'Connor, W.; O'Connor, E.; Barnes, M.; Miller, M.; Gardener, H.; Stannard, S. (Journal of Science and Cycling, 2022)
This study was designed to test whether adaptation to a CHO-restricted diet affects physical capacity during prolonged exercise. It is hypothesised that chronically reducing an individual`s dietary carbohydrate intake during training will increase their maximal rate of fatty acid oxidation during subsequent exercise compared to a chronic high carbohydrate diet. Thirteen highly trained endurance athletes (eight males, VO2max 66.0 ± 9.5 ml/kg/min, five females VO2max 50.6 ± 8.4 ml/kg/min) consumed a high (>5 g CHO/kg/day) or low (<2 g CHO/kg/day) carbohydrate training diet for four weeks in a randomized cross-over design. Performance was measured after a 24 h high carbohydrate "loading" regime, through a self-paced time trial to complete a fixed workload equivalent to five hours at a workload calculated to elicit 55% VO2max. Although time to completion was not significantly different between diets, the average absolute (watts) and relative (W/kg) power outputs were significantly better on the carbohydrate restricted diet (p = 0.03 and 0.02 respectively). Both sexes responded similarly in terms of performance whilst only women significantly improved body composition when carbohydrate was restricted (p = 0.02). Results from this study highlight that when carbohydrate is restricted during training, trained endurance athletes show improved ultra-endurance performance relative to their body mass.